Uslub Khabari Bagi Terminologi Gegaran (zalzalah) Dalam Al-quran - Khairul Asyraf Mohd Nathir; Rosni Samah; Mohd Adi Amzar Mohammad Nawawi; Muhamad YazidAbdul Majid; Amani Nawi; Bushro Bakri (Usuli Faqih Research Center, 2024)
Al-Qanatir: International Journal of Islamic Studies Volume 33 Issue 5 Page (1–18)